Morphoanatomical, functional and evolutionary traits conditioning the adaptability of leguminosae in an edaphoclimatic gradient - Fagundes, Nathalle Cristine Alencar (2019)
This thesis aimed to assess relationships among phylogenetic diversity, functional traits and adaptive success of the family Leguminosae, represented by variables related to the structure and dynamics of this family in an edaphoclimatic gradient across the north / south direction of the Minas Gerais state. Said gradient comprises deciduous forest formations, in the northern portion of the state, semideciduous forests in the Campo das Vertentes mesoregion and ombrophilous nebular forests in southern Minas Gerais. To achieve our aim, we used data from two forest dynamics inventories (15 years and three measurements), structural data about the legumes in the sampled plots, chemical and textural soil variables, the nineteen bioclimatic variables from WorldClim, phylogenetic beta diversity and hydraulic-related functional traits collected from legume species within the forest plots. In the first chapter we fitted generalized linear mixed-effects models with all the aforementioned variables, and in the second chapter, with hydraulic-related wood functional traits, soils and using only data from Seasonally Dry Tropical Forest (SDTF) formations. From our results, we could observe that Leguminosae structure was strongly related to the sampled environmental variables, especially with altitude, which synthesizes climate and humidity, as well as to phylogenetic distance. This family distribution revealed conditioned to dry, hot and fertile environments. We found conspicuous functional specialization in the observed deciduous forests, with a decrease in specialization towards the semideciduous formations, and the presence of more generalist legume species, in terms of habitat, in the ombrophilous forests. The individuals collected in the deciduous forests presented lower vulnerability to cavitation by water vapour pressure deficit than those from semideciduous forests. Legume individuals from deciduous forests showed conservative ecological strategies, but with fast growth, while the individuals from the semideciduous formations revealed a functionality more compatible with an acquisitive strategy, but with slower growth. Thus, although usually regarded as a homogeneous biome, the SDTFs present distinct ecological strategies in response to seasonality. In semideciduous forests, despite the predominance of acquisitive species, we also found conservative and rapid-growth pioneer species. However, we recognised an increase in slow-growth legume species in the semideciduous forests dynamics, showing that climate change may be favou ring species that are tolerant to high temperatures and water deficit, influencing the floristic composition of semideciduous forests. Beyond increasing the understanding of the biogeographic patterns involved in the Leguminosae distribution, these results can provide insights about the Leguminosae responses to climate change and, consequently, they can be used to establish plant community conservation strategies.